Peningkatan kualitas pelayanan rawat jalan di rumah sakit indonesia melalui manajemen lean healthcare: A systematic review - Priladiantika, Berta Ivana; Intiasari, Arih Diyaning; Mulyanto, Joko (Holistik Jurnal Kesehatan, 2025)
Background: Lean management, part of the Toyota Production System, is now applied across various industries to improve service quality. The implementation of lean in hospitals aims to enhance efficiency, reduce the length of hospital stays, and minimize medical errors, although the outcomes vary depending on factors such as leadership, training, and staff engagement. Purpose: To examine the improvement of the quality of outpatient services in Indonesian hospitals through lean healthcare management. Method: This article uses a PICO approach and follows the PRISMA guidelines, starting with a database search that yielded 256 articles. These were then screened based on inclusion and exclusion criteria, resulting in 12 relevant articles. The selection process included the removal of duplicate articles, screening of titles and abstracts, and full-text evaluation. Results: The implementation of lean management in Indonesian hospitals was carried out by observing and recording service flow from registration to payment, then analyzing service time based on Value-Added and Non-Value-Added Activities using Visual Stream Mapping or spaghetti diagrams, and discussing solutions through the 5 Whys and Fishbone Analysis methods. Conclusion: Lean management has been proven effective and suitable for application in hospital outpatient services to improve efficiency by eliminating waste and optimizing systems.   Keywords: Healthcare; Hospital; Lean Management; Outpatient.   Pendahuluan: Manajemen Lean, bagian dari Toyota Production System, kini diterapkan di berbagai industri untuk meningkatkan kualitas layanan. Implementasi manajemen lean di rumah sakit bertujuan untuk meningkatkan efisiensi, mengurangi lama pelayanan, dan meminimalkan kesalahan medis, meskipun hasilnya bervariasi tergantung pada faktor-faktor seperti kepemimpinan, pelatihan, dan keterlibatan staf. Tujuan: Untuk mengkaji peningkatan kualitas pelayanan rawat jalan di rumah sakit Indonesia melalui manajemen lean healthcare. Metode: Artikel ini menggunakan pendekatan PICO dan mengikuti pedoman PRISMA, dimulai dengan pencarian database yang menghasilkan 256 artikel. Artikel-artikel ini kemudian disaring berdasarkan kriteria inklusi dan eksklusi, menghasilkan 12 artikel yang relevan. Proses seleksi mencakup penghapusan artikel duplikat, penyaringan judul dan abstrak, serta evaluasi fulltext. Hasil: Implementasi manajemen lean di rumah sakit Indonesia dilakukan dengan mengamati dan mencatat alur layanan dari pendaftaran hingga pembayaran, kemudian menganalisis waktu layanan berdasarkan Aktivitas Bernilai Tambah (Value-Added) dan Aktivitas Tidak Bernilai Tambah (Non-Value-Added) menggunakan Visual Stream Mapping atau diagram spageti, dan mendiskusikan solusi melalui metode 5 Whys dan Analisis Fishbone. Simpulan: Manajemen lean terbukti efektif dan cocok untuk diterapkan di layanan rawat jalan rumah sakit untuk meningkatkan efisiensi dengan menghilangkan pemborosan (waste) dan mengoptimalkan sistem.   Kata Kunci: Healthcare; Manajemen Lean; Rawat Jalan; Rumah Sakit.